Perceptions on violence against women, care of victims and role of the obstetrician of the Regional Councils of Peru, 2021 - Condor, Melanie (2023)
Introduction: Violence against women is a public health problem and is addressed by health professionals in clinical care. Thus; It is important to know the perceptions of the professional, mainly the obstetrician, who has more contact with women, since they will influence their work.Objective: Determine the perceptions of violence against women, care of victims and the role of the obstetrician of the Regional Councils of Peru, 2021Materials and Methods: Study with a qualitative approach and phenomenological design, 11 obstetricians members of the different CROs of Peru participated. Data collection was through semi-structured interviews and content analysis was performed with the Atlas/Ti 9 software. Approved by the UNMSM ethics committee.Results: The CRO obstetricians stated that violence against women is a public and social health problem conditioned by machismo in a transversal way in society, which remains due to the deficient role of the State. In addition, it impacts on women's health from compromising their lives to their autonomy and self-care. They stated that comprehensive care is a holistic care of the person together with other professionals and that it has been partially carried out. In addition, the obstetrician plays an important role in the care of victims considering their competencies, prioritizing the care area; compared to proposals from other areas to contribute to the eradication of violence against women.Conclusions: Obstetricians perceive violence against women as an important public health problem in which they play a significant role for its eradication, mainly in the care area, providing comprehensive care; however, there is still a clinical vision of the problem on the part of the institution and the prioritization of other issues.